Fat label compared with fat content: gastrointestinal symptoms and brain activity in functional dyspepsia patients and healthy controls. Issue 1 (18th June 2018) - Lee, In-Seon; Kullmann, Stephanie; Scheffler, Klaus; Preissl, Hubert; Enck, Paul
ABSTRACT: Background: High-fat meals are associated with dyspeptic symptoms in functional dyspepsia (FD) patients. It is still unclear how fat is processed, or how FD symptoms and neuronal activities are modulated by psychological factors. Objective: We investigated brain activity by functional magnetic resonance imaging (fMRI) after the ingestion of high- and low-fat foods with correct/incorrect fat information. Design: We compared 12 FD patients and 14 healthy controls (HCs). We recorded resting-state fMRI on four different days before and after ingestion of four yogurts (200 mL, 10% or 0.1% fat, "low fat" or "high fat" label). Results: FD patients showed more pronounced dyspeptic symptoms than did HCs, and symptoms were relieved less after consuming high fat–labeled yogurt than low fat–labeled yogurt, irrespective of the actual fat content. This is indicative of either a placebo effect of low-fat information or a nocebo effect of high-fat information on symptom expression. FD patients showed greater activity than did HCs in occipital areas before and after ingestion regardless of fat content and label, as well as greater activity in the middle frontal gyrus before ingestion. In addition, functional connectivity (FC) from the insula to the occipital cortex (I-O) increased after high fat ingestion and decreased after low fat ingestion in FD patients. FC from the insula to the precuneus (I-P) was higher in FD patients than in HCs after ingestion of low fat–labeled yogurt. In FD patients, I-O FC negatively correlated with nausea and I-P FC with FD symptom intensity, food craving, and depression. Conclusions: Our results endorse the importance of psychological perception of food on the incidence of dyspeptic symptoms and on the altered brain activities. These findings show the importance of cognitive components in perceptions of fat, food craving, depression, and brain functions in pathophysiologic mechanisms of FD. This trial was registered at clinicaltrials.gov as NCT02618070.